Adsorptive behavior of the rare earth elements Ce and La on a soybean pod derived activated carbon: application in synthetic solutions, real leachate and mechanistic insights by statistical physics modeling (2023)
In this study, we aimed to produce a sustainable and efficient powdered activated carbon (SP-AC) and evaluate its adsorptive abilities to uptake and recover rare earth elements (REEs) from synthetic solutions containing lanthanum (La(III)) and cerium (Ce(III)), and real leachate, from phosphogypsum, containing several REEs. The adsorbent material was subjected to several characterization techniques to understand its physicochemical and adsorptive properties. The characterization results indicated that the activated carbon prepared in this work possesses a specific surface area, pore volume, and average pore diameter of 614 m2g−1, 0.121 cm3g−1, and 3.65 nm, respectively. Interestingly, the adsorbent material exhibited a highly negatively charged surface which was extremely beneficial for La(III) and Ce(III), which are positively charged and therefore were easily attracted to each other. The kinetic data were well fitted by pseudo-second-order, while the Liu model agreeably fitted equilibrium data. The maximum adsorption capacities for Ce(III) and La(III) were 107.7 and 127.2 mg g−1 at 298 K, respectively. The thermodynamic data indicated that the adsorption systems between SP-AC and both REEs were favorable, spontaneous, and exothermic. The adsorption mechanisms between SP-AC and the two REEs were proposed based on the experimental results, adsorbent characteristics, and statistical physics approach. Pore filling and ion exchange were the main mechanisms, although surface complexation was also involved. Finally, the SP-AC was employed to recover many REEs from real phosphogypsum leachate, demonstrating that SP-AC can selectively recover REEs in the real process.